Biomimetic Superhydrophobic/Superoleophilic Highly Fluorinated Graphene Oxide and ZIF-8 Composites for Oil-Water Separation - Jayaramulu, Kolleboyina; Datta, Kasibhatta Kumara Ramanatha; Rösler, Christoph; Petr, Martin; Otyepka, Michal; Zboril, Radek; Fischer, Roland A (Angewandte Chemie (International ed. in English), 2016)
Superhydrophobic/superoleophilic composites HFGO@ZIF-8 have been prepared from highly fluorinated graphene oxide (HFGO) and the nanocrystalline zeolite imidazole framework ZIF-8. The structure-directing and coordination-modulating properties of HFGO allow for the selective nucleation of ZIF-8 nanoparticles at the graphene surface oxygen functionalities. This results in localized nucleation and size-controlled ZIF-8 nanocrystals intercalated in between HFGO layers. The composite microstructure features fluoride groups bonded at the graphene. Self-assembly of a unique micro-mesoporous architecture is achieved, where the micropores originate from ZIF-8 nanocrystals, while the functionalized mesopores arise from randomly organized HFGO layers separated by ZIF-8 nanopillars. The hybrid material displays an exceptional high water contact angle of 162° and low oil contact angle of 0° and thus reveals very high sorption selectivity, fast kinetics, and good absorbencies for nonpolar/polar organic solvents and oils from water. Accordingly, Sponge@HFGO@ZIF-8 composites are successfully utilized for oil-water separation.
Keywords: superhydrophobicity; zeolite imidazole frameworks; superoleophilicity; highly fluorinated graphene oxide; oil-water separation